Late Wisconsinan Sedimentation in the Québec City Region: Evidence for Energetic Subaqueous Fan Deposition During Initial Deglaciation - Cummings, Don; Occhietti, Serge (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractIn the St. Lawrence Valley just west of Québec City, initial deglaciation was accompanied by an energetic northward discharge of meltwater into a body of water, possibly subglacial, that was present in the axis of the valley. At Pointe Saint-Nicolas, a thick (> 35 m) ice-proximal sandy subaqueous fan was deposited during this event. The subaqueous fan is composed primarily of northwest-dipping turbidite sheets, with minor hyperconcentrated underflow channel fills and gravel-outwash deposits. By 11 200 14C BP, subaqueous fan sedimentation had stopped, and massive to rhythmically interbedded glaciomarine muds were being deposited. Introduction of muds into the basin promoted subaqueous slope failure and debris flowing locally. Between 10 950 and 10 800 14C BP, the Laurentide Ice Sheet readvanced southward onto the south shore, and deposited the subglacial St. Nicolas Till. With continued isostatic rebound and associated forced regression, tidal currents began to rework emergent coastal zones, and fluvial systems started to incise their valleys.